The Weimar Manuscript by Martynas Liudvikas Rėza - Citavičiūtė, Liucija (Tautosakos darbai, 2018)
The Goethe and Schiller Archive in Weimar contains some valuable Lithuanian cultural artefacts, including the manuscript collection of Lithuanian folksongs, which Liudvikas Rėza sent to Johann Wolfgang von Goethe in 1820. That is the so-called Weimar manuscript. Goethe noted in his diary of having received this manuscript; however, Rėza remained forever unaware of the fact. The first to publish information in periodical about the manuscript being in Weimar was a historian from Konigsberg Erich Jenisch in 1931, and the first Lithuanian to see it was Juozas Eretas in 1933. However, the latter only copied the titles of the songs. The last to mention the manuscript was Albinas Jovaišas in 1969; but he had not seen it himself. The manuscript was not included into Lithuanian bibliographies and subsequently sank into oblivion, his fate becoming the legendary subject. Nevertheless, a copy of the manuscript brought to Lithuania in 2017 by the author of this article clearly testifies this being a collection of 89 folksongs ready for publication, which was printed in 1825 with only several minor corrections and slight editing. The song translations into German suffered the heaviest editing. The manuscript does not contain any handwritten remarks by Goethe or anybody else.